The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/s11010-020-03937-x
|View full text |Cite
|
Sign up to set email alerts
|

MSC-AS1 knockdown inhibits cell growth and temozolomide resistance by regulating miR-373-3p/CPEB4 axis in glioma through PI3K/Akt pathway

Abstract: Long non-coding RNAs (lncRNAs) have been widely reported to regulate the development and chemoresistance of a variety of tumors. Temozolomide (TMZ) is a first-line chemotherapy for treatment of glioma. However, the effect and the regulatory mechanism of lncRNA MSC-AS1 (MSC-AS1) in TMZ-resistant glioma remain unrevealed. Levels of MSC-AS1, microRNA-373-3p (miR-373-3p), and cytoplasmic polyadenylation element binding protein 4 (CPEB4) were determined by quantitative real-time polymerase chain reaction (qRT-PCR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
(49 reference statements)
1
20
0
Order By: Relevance
“…MSC-AS1 was found to regulate the tumor progression by inhibiting miR-124 expression to increase CDK6 expression in osteosarcoma [ 21 ]. Moreover, MSC-AS1 acted as a role of carcinogenic factor in glioma by sponging miR-373-3p and upregulating CPEB4 [ 22 ]. Li et al reported that the expression of miR-325 was reduced in CRC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSC-AS1 was found to regulate the tumor progression by inhibiting miR-124 expression to increase CDK6 expression in osteosarcoma [ 21 ]. Moreover, MSC-AS1 acted as a role of carcinogenic factor in glioma by sponging miR-373-3p and upregulating CPEB4 [ 22 ]. Li et al reported that the expression of miR-325 was reduced in CRC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, our KEGG pathway analysis suggested that the differentially expressed lncRNAs may regulate DV development via the PI3K/Akt pathway. Coincidentally, dysregulation of MSC-AS1 expression was found to promote tumor progression in glioma and osteosarcoma through the PI3K-Akt pathway [ 32 , 33 ], which may further support the important role of MSC-AS1/PI3K-Akt pathway in DV to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-AS1 induces PGK1 expression and accelerates the progression of HCC ( 30 ). In addition, MSC-AS1 has a similar role in gliomas ( 31 ), gastric cancer ( 32 ), renal clear cell carcinoma ( 33 ), and pancreatic cancer ( 34 ). TMEM220-AS1, AC015908.3, AC009005.1, and AL031985.3 have been reported in a signature predictive of overall survival.…”
Section: Discussionmentioning
confidence: 99%